2012
DOI: 10.1637/10189-041012-reg.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Virus Strain Characteristics on Early Detection of Highly Pathogenic Avian Influenza Infection in Commercial Table-Egg Layer Flocks and Implications for Outbreak Control

Abstract: Early detection of highly pathogenic avian influenza (HPAI) infection in commercial poultry flocks is a critical component of outbreak control. Reducing the time to detect HPAI infection can reduce the risk of disease transmission to other flocks. The timeliness of different types of detection triggers could be dependent on clinical signs that are first observed in a flock, signs that might vary due to HPAI virus strain characteristics. We developed a stochastic disease transmission model to evaluate how trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…It is important to note that the RRT‐PCR disease detection trigger evaluated here is a form of targeted active surveillance intended to result in the earliest time to detection in order to reduce the spread of HPAI virus to another poultry premises . Efficient HPAI disease detection is conditional on the presence of chickens infected with HPAI virus in the dead bird pool, in combination with rapidly increasing mortality observed for most HPAI strains.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is important to note that the RRT‐PCR disease detection trigger evaluated here is a form of targeted active surveillance intended to result in the earliest time to detection in order to reduce the spread of HPAI virus to another poultry premises . Efficient HPAI disease detection is conditional on the presence of chickens infected with HPAI virus in the dead bird pool, in combination with rapidly increasing mortality observed for most HPAI strains.…”
Section: Discussionmentioning
confidence: 99%
“…In order to estimate the number of contaminated eggs laid by HPAI‐infected chickens in a flock to be presented for breaking, a conservative assumption was made that the flock is in an infected, but undetected, disease state. A stochastic, within‐flock, disease spread simulation model was used to simulate the spread of three different strains of HPAI virus after the introduction of one infected chicken into the flock (house) of 100,000 table‐egg‐layer hens . The three HPAI virus strains were chosen to represent the natural variability inherent in the length of the infectious period, which impacts within‐flock virus transmission characteristics and, ultimately, the time to detection of HPAI infection in the flock.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For an example of the latter, a within-flock model showed that vaccines conferring incomplete protection could counterintuitively increase the infectiousness of a flock, by delaying the time to detection and depopulation (Savill et al, 2006). Within-flock models have also been used to: (1) infer important events – such as the day of introduction – from mortality data (Bos et al, 2007), (2) estimate the risk of HPAIV transmission due to the movement of poultry-industry products from monitored flocks (i.e., flocks not known to be infected with HPAIV) into commerce (Malladi et al, 2012), (3) estimate important epidemiological parameters (Bouma et al, 2009) and (4) estimate mean time to detection for HPAIV strains under different surveillance-detection triggers (Weaver et al, 2012). …”
Section: Transmission Within Poultry Flocksmentioning
confidence: 99%